POTENSI JALAN HUTAN DALAM AKSELERASI EROSI TANAH DI KALIMANTAN BARAT - Djaban Tinambunan (Jurnal Penelitian Hasil Hutan, 1988)
A  study   on  the potential  of  forest   roads for  accelerating  soil  erosion on was carried  out  at four logging  companies in  West Kalimantan  in 1987.  Road  elements measured  in the  field  are those  related  to  the Universal Soil Loss Equation factors such as road openings,   surfaces,  slopes, and  ditches, culverts,  cuts,  fills, diversion  ditches,  and  the  incidence  of vegetation.                                                                                                                            The  results  showed   that  forest  soil  disturbances   caused  by  road  construction   create ground  condition   which  has high potentials   for  accelerating  erosion.   Factors  that  caused  this problem,   as identified   in the  field,  are: log and steep slopes,  wide ground  openings,  and  bare soil surfaces,   in addition  to  the  originally  sensitive  to erosion  soil  type,  and  hot and wet weather.Further  study   is necessary  in order  to  find  the real amount   of soil erosion occured  in forest  roads in West Kalimantan. Qualitatively  it is known  to be  high but  quantitatively   it needs  to  be found